Circadian rhythms of gene expression at leaves of vegetating plants - Tsygankova, V.A. (Фактори експериментальної еволюції організмів, 2010)
Abstract
Using DOT-blot hybridization DNA with RNA the analysis of degree homology of
products of gene expression (cytoplasmical mRNAs) is fulfilled from the cells of
dicotyledonous (soya, pea) and monocotyledonous plants (wheat, corn) leaves, after their
separation from plants in an early period with weak photosynthesis (at 5 a.m.), in a
middle period (at 2 p.m.) with strong photosynthesis and in the evening period with weak
photosynthesis to the relation to mRNA from plant leaves, being in a dark phase (at 2 a.m.).
It is shown that divergence in populations between experience and control begins in the
early morning at weak sunshine, sharply increases at daily light (at 2 p.m.) and goes out
on sunset. It is assumed that these changes occur by the “windmill” switching genes,
belonging to one family, but possessing different activity due to location them under
promoters of different force (promoters of weak, moderate and strong force) and that
plasticity (maneuverability) of plant adaptation to the environment is arrived by such
mechanism. Методом ДОТ-блот гибридизации ДНК с РНК проведен анализ степени гомологии продуктов экспрессии генов (цитоплазматических мРНК) из клеток листьев
двудольных (сои, гороха) и однодольных растений (пшеницы, кукурузы), после
отделения их от растений в ранний период со слабым фотосинтезом (5 утра),
в средний период (14 часов дня) с сильным фотосинтезом и в вечерний период с
угасающим фотосинтезом по отношению к мРНК листьев растений, находящихся
в темновой фазе (2 часа ночи — контроль). Показано, что разница в популяциях
между опытом и контролем начинается ранним утром при слабом солнечном
освещении, резко усиливается при дневном освещении (14 часов дня) и угасает на
заходе солнца. Предполагается, что эти изменения происходят путем “веерного”
переключения генов, принадлежащих к одному семейству, но обладающих разной
активностью за счет расположения их под промоторами разной силы (промоторах
слабой силы, умеренной силы и сильных промоторах) и что путем такого механизма
достигается пластичность (маневренность) адаптации растений к окружающей
среде. Методом ДОТ-блот гібридизації ДНК із РНК проведено аналіз ступеня гомології продуктів експресії генів (цитоплазматичних мРНК) з клітин листків дводольних (сої, гороху) і однодольних (пшениці, кукурудзи) рослин, після відділення їх
від рослин в ранній період зі слабким фотосинтезом (о 5-й годині ранку), в середній
період (о 14-й годині) з сильним фотосинтезом і в вечірній період із згасаючим
фотосинтезом по відношенню до мРНК листків рослин, що знаходились в темновій
фазі (о 2-й години ночі — контроль). Показано, що різниця в популяціях між дослідом і контролем починається вже вранці при слабкому сонячному освітленні, різко
посилюється при денному освітленні (о 14-й годині дня) та знижується на заході
сонця. Припускається, що ці зміни відбуваються шляхом “віяльного” переключення
генів, що належать до однієї родини, але виявляють різну активність за рахунок
розташування їх під промоторами різної сили (промоторах слабкої сили, помірної
сили та сильних промоторах) і що шляхом такого механізму досягається пластичність (маневреність) адаптації рослин до оточуючого середовища.